Melia dubia An indigenous tree species for industrial agroforestry in India - Chavan, S.B.; Vishnu, R.; Kumar, Naresh; Kumar, Dhiraj; Sirohi, Chhavi; Handa, A.K. (Indian Farming, 2021)
Malia based agroforestry systems is have greater potential to meet the ever rising demand for food and wood. In addition to it has the potential to reverse land degradation, sequester carbon and recover site productivity through interactions among trees, soil, agricultural crops and livestock and thus restore environment and enhance productivity. The standard and recommended package and practices of Melia dubia could help to farmers for achieving higher diversification of traditional cropping systems and industrial required raw material.